2004
DOI: 10.1557/jmr.2004.0269
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion and N co-doped TiO2 as a visible-light photocatalyst

Abstract: Powders of TiO2 doped with a metal ion and N species were prepared by a polymerized complex method and the visible-light photocatalytic activities of the products are investigated. Of the metal ions studied (K+, Ca2+, Sr2+, Ba2+, Nb5+, Fe3+, Zn2+, and Al3+), the photocatalyst prepared with Sr2+ exhibits the highest activity for acetaldehyde decomposition under visible-light irradiation. Results obtained from x-ray photoelectron spectroscopy (XPS) and electron spin resonance (ESR) analyses suggest that the dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 15 publications
3
59
0
Order By: Relevance
“…[59][60][61] Subsequently, nitrogen-doped TiO 2 has attracted considerable attention. [62][63][64] In fact, similar photocatalysts sensitive to visible light have already been reported in 1986.…”
Section: Visible-light-sensitive Tiomentioning
confidence: 99%
“…[59][60][61] Subsequently, nitrogen-doped TiO 2 has attracted considerable attention. [62][63][64] In fact, similar photocatalysts sensitive to visible light have already been reported in 1986.…”
Section: Visible-light-sensitive Tiomentioning
confidence: 99%
“…Their effects on the properties of the doped samples have been reported. Some research groups attempted to modify TiO 2 such that it showed response to visible wavelength through the use of oxygen-vacant TiO 2 [12], nonmetal-doped TiO 2 [13,14], and metal-nonmetal codoped TiO 2 [15] particles that have significant photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…co-doping with nitrogen and various metal ions, has been studied [26,27], and to a lesser extent carbon and tungsten co-doping [28].…”
mentioning
confidence: 99%